Energy and Environmental Indicators of the Combustion of High-moisture Fuels Based on Typical Municipal and Industrial Wastes; Энерго-ресурсоэффективность в интересах устойчивого развития - Vershinina K. Yu. Kseniya Yurievna (Экоэнергетика, 2018)
Заглавие с экрана